An approach to the legal statuts of acllas and prostitutes during the inca times according to the Comentarios Reales - Carrasco Ligarda, Rosa (2015)
This study presents the norms that regulated the life of the Chosen Ones (Sun virgins) and the prostitutes during the Inca times, according to the work written by Inca Garcilaso de la Vega. All references are from his Comentarios reales de los Incas [1609 (1st edition)-1616 (2nd edition)]  published in Lima (1985) by the Peruvian National Library. The subjects explained here are contradicted, enlarged or complemented by the chronicles of Francisco de Xerez (1534), Juan deBetanzos [1551], Pedro Cieza de León [1553], Juan de Matienzo [1567], Pedro Pizarro [1571], José de Acosta [1590], Blas Valera [1588 (?)], Miguel Cabello de Balboa [1586], Martín de Murúa [1590], Antonio de Herrera (1615), Guamán Poma de Ayala [1615], Juan de Santa Cruz Pachacuti [1613], Bernabé Cobo [1653] among others.